2011
DOI: 10.5551/jat.6346
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Bilirubin Concentration, Coronary Endothelial Function, and Inflammatory Stress in Overweight Patients

Abstract: Aim:Bilirubin has antioxidant properties and may protect against atherosclerosis and coronary heart disease (CHD). Further, in patients with metabolic syndrome, hyperbilirubinemia is associated with attenuation of insulin resistance. The aim of the present study was to determine the relationship between serum bilirubin concentration and coronary endothelial function in overweight patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 47 publications
5
37
0
1
Order By: Relevance
“…Estos hallazgos han sido replicados en diversos grupos étnicos 41 . Se postula que la bilirrubina ejerce un efecto protector antioxidante y/o antiinflamatorio 42 . La bilirrubina tiene mayor capacidad en reducir la oxidación lipídica que el glutatión y la vitamina E 43,44 .…”
Section: Discussionunclassified
“…Estos hallazgos han sido replicados en diversos grupos étnicos 41 . Se postula que la bilirrubina ejerce un efecto protector antioxidante y/o antiinflamatorio 42 . La bilirrubina tiene mayor capacidad en reducir la oxidación lipídica que el glutatión y la vitamina E 43,44 .…”
Section: Discussionunclassified
“…Moraes et al (112) also showed that the endogenous HO-derived by-products (bilirubin, biliverdin, and carbon monoxide) suppressed the prooxidant effect of heme and the proliferation of VSMC via modulation of NADPH oxidase activity. Moreover, higher serum bilirubin concentrations are also independently and positively correlated with improved FMD in overweight Japanese patients (197), and a negative relationship between bilirubin levels and incidence of hypertension is reported in a Korean population (26). In the latter study, subjects with lower bilirubin levels (Ͻ1.1 mg/dl) had higher mean arterial pressures and serum creatinine concentrations after adjustment for confounders.…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 94%
“…Flow-mediated dilation was significantly greater in overweight patients with the greatest bilirubin concentrations (Ͼ0.77 mg/dl), further suggesting that bilirubin protects against endothelial dysfunction (197). Elevated serum bilirubin concentrations are also associated with improved endothelium-dependent function of coronary arteries in patients without coronary heart disease (CHD) (196).…”
Section: Potential Protective Effects Of Bilirubinmentioning
confidence: 98%
“…Investigations in GS subjects, and experiments utilizing the rat model of hyperbilirubinaemia (Gunn rat), show protection from ex vivo [9,10] and in vivo [11] oxidation, coronary atherosclerosis [12], protection from thiol and protein oxidation [13] as well as anti-inflammatory [14] or anti-proliferative properties [15,16] of bilirubin.…”
Section: Introductionmentioning
confidence: 99%